Assessing the Potential Adoption of Quinoa for Human Consumption in Central Malawi - Gardner, Morgan; Maliro, Moses F. A.; Goldberger, Jessica R.; Murphy, Kevin M. (Frontiers in Sustainable Food Systems, 2019)
This study assesses the potential adoption of quinoa for consumption in central Malawi. Environmental, economic, and social problems are prevalent in this region dependent on subsistence agriculture. Quinoa is conceptualized as a new agricultural innovation. If successfully adopted, quinoa may have the potential to provide additional nutrition, crop diversification, and added value as an export crop for smallholder farms. Everett Rogers' Diffusion of Innovations framework seeks to explain how, why, and at what rate individuals or societal groups adopt new ideas and technology over time. To assess the potential adoption of quinoa as an alternative food source in central Malawi, this exploratory study focuses on two aspects of the Diffusion of Innovations model: perceived compatibility (an innovation attribute) and change agents' promotion efforts. With an emphasis on the local-level experiences of regional farmers and extension specialists, data were gathered to evaluate the adoption potential of a new innovation (quinoa) and the potential diffusion of information between extension programs and local farmers. Results showed that adoption potential in this region is positive, with a focus on regular and consistent extension visits, and participatory research between researchers, extension, and villagers.